The gender congruency effect in Catalan–Spanish bilinguals: Behavioral and electrophysiological evidence. Issue 5 (3rd November 2020) - Paolieri, Daniela; Demestre, Josep; Guasch, Marc; Bajo, Teresa; Ferré, Pilar
Abstract: The present study examines whether processing a word in one language is affected by the grammatical gender of its translation equivalent in another language. To this end, a group of Catalan–Spanish bilinguals performed a translation–recognition task while event-related potentials (ERPs) were recorded. Participants were presented with Catalan and Spanish pairs of words and had to decide if they were translation equivalents. Correct translations included words that were gender congruent ( estiu MAS / verano MAS –summer) or gender incongruent ( tardor FEM / otoño MAS –autumn). The behavioral results showed that participants were faster and more accurate in the gender-congruent condition than in the incongruent condition. The ERP data showed a reduced N400 for the congruent condition. The facilitative effect of gender congruency observed in this study constitutes evidence of the obligatory access to grammatical gender information during bare noun processing and suggests that the bilinguals' gender systems interact, even in highly proficient early bilinguals.